Thermodynamic analysis of the solubility of clozapine in organic solvents. (July 2021) - Yu, Shuai; Cheng, Yan; Du, Shichao; Wang, Yan; Xue, Fumin; Xing, Wenguo
Graphical abstract: Highlights: Solubility data of clozapine in eighteen pure organic solvents were determined. Different thermodynamic models were used to correlate solubility data. Solubility increase with the increasing of temperature. Dissolution properties of clozapine were calculated based on the Wilson model. Abstract: The solid-liquid equilibrium solubility of clozapine in eighteen organic solvents ( i.e., methanol, ethanol, n -propanol, i -propanol, n -butanol, i -butanol, s -butanol, n -pentanol, i -pentanol, acetone, 2-butanone, acetonitrile, N, N -dimethylformamide, tetrahydrofuran, chloroform, ethyl formate, methyl acetate, and ethyl acetate) was determined using a gravimetric method over a temperature ranging from 278.15 K to 323.15 K at atmospheric pressure. The modified Apelblat equation, λh equation, NRTL equation, and Wilson equation were selected to correlate the solubility data. The fitting degree of thermodynamic models was evaluated by the relative average deviation, and root mean root mean square deviation. Dissolution properties, including enthalpy, entropy, and Gibbs energy changes of clozapine were evaluated by the Wilson model. The solubility data, thermodynamic parameters and dissolution properties for clozapine will be of crucial guiding value for the optimization of the industrial crystallization process.